b n answer to the Pope's criticism of Buddhism /c - Thinley Norbu (b, 2012)
The author provides a pointed critique of the Buddhism chapter of Pope John Paul II's 1994 best seller, Crossing the Threshold of Hope. In responding to the false charges of Buddhists' indifference to the world and rejection of reality, Norbu clarifies the Buddhist doctrines of detachment and enlightenment. In addition, he covers the topics of good and evil, human nature, karma, cosmology, and dualistic mind, bringing them into conversation with the Christian perspective as presented by the Pope.
Keywords: Buddhism -- Doctrines; Buddhism -- Relations -- Christianity; Christianity and other religions -- Buddhism